2019
DOI: 10.1039/c9sc03033f
|View full text |Cite
|
Sign up to set email alerts
|

Alkynylation of radicals: spotlight on the “Third Way” to transfer triple bonds

Abstract: This review explores the alkynylation of radicals as approach for the flexible and efficient synthesis of alkynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 142 publications
(107 reference statements)
1
73
0
Order By: Relevance
“…The CF 3 -radical released can then add to an alkene to sustain a chain reaction, 17,18,19 and accordingly, reagent 2a was successfully applied to the a-trifluoromethyl-b-alkynylation of alkenes (1,2-difunctionalization). 20,18 We were very pleased to find that the cascade worked as planned, and reaction optimization (see Supplemental Information for full screening) revealed that this sequence is best conducted by using a a 0 -azobisisobutyronitrile as an initiator (30 mol %) in ethyl acetate as the solvent at 85 C by using 2 equivalents of the alkynyl triflone reagent 2a. The desired product, boronic ester 3a, was isolated in 72% yield, and the 1,2-difunctionalization product 21 that could be formed by direct trapping of the b-trifluoromethyl alkyl radical with reagent 2a was not identified.…”
Section: Resultsmentioning
confidence: 99%
“…The CF 3 -radical released can then add to an alkene to sustain a chain reaction, 17,18,19 and accordingly, reagent 2a was successfully applied to the a-trifluoromethyl-b-alkynylation of alkenes (1,2-difunctionalization). 20,18 We were very pleased to find that the cascade worked as planned, and reaction optimization (see Supplemental Information for full screening) revealed that this sequence is best conducted by using a a 0 -azobisisobutyronitrile as an initiator (30 mol %) in ethyl acetate as the solvent at 85 C by using 2 equivalents of the alkynyl triflone reagent 2a. The desired product, boronic ester 3a, was isolated in 72% yield, and the 1,2-difunctionalization product 21 that could be formed by direct trapping of the b-trifluoromethyl alkyl radical with reagent 2a was not identified.…”
Section: Resultsmentioning
confidence: 99%
“…Vinylation of Free Radical . As several other hypervalent iodine transfer reagents, [65,66] VBXs proved to be good electrophilic radical acceptors. With the recent advent of photoredox catalysis several groups have started to apply VBX reagents under such conditions.…”
Section: Vbxmentioning
confidence: 98%
“…[34][35][36][37][38][39][40] Therefore, hypervalent iodine compounds have found wide application as efficient oxidative reagents and ligand transfer reagents in many reactions. [41][42][43][44][45][46][47][48][49] In fact, numerous oxidative reactions, benzyne-mediated reactions, and new bondforming reactions, such as carbon-carbon, carbon-heteroatom, or hetero-heteroatom bonds, have been accomplished using hypervalent iodine reagents under metal-free conditions. In particular, these reagents have been used for various ring construction reactions.…”
Section: Introductionmentioning
confidence: 99%